Development of the Bonding Technology of Modern Automotive Materials with Environmentally Friendly Solutions - Zoltan Weltsch; Ferenc Tajti; Miklós Berczeli (Communications, 2024)
The significance of bonding technology for modern vehicle structural materials is increasingly acknowledged, driven by the adoption of new materials to reduce weight. This is important not only for quality and economic reasons but to address environmental pollution, as well. Traditional joining methods like riveting, screwing, welding, and brazing, are often unsuitable or limited for modern materials. Soldering, an economical and almost waste-free technology, is becoming more widespread. Through optimization, it achieves a strong, durable bond. There is a potential to favourably alter interface properties, including using high energy density surface treatments. Research showed that the laser surface treatment of high-strength steel sheets could improve the mechanical properties of soldered joints.